Factors affecting actualisation of the WHO breastfeeding recommendations in urban poor settings in Kenya. Issue 3 (17th December 2014) - Kimani‐Murage, Elizabeth W.; Wekesah, Frederick; Wanjohi, Milka; Kyobutungi, Catherine; Ezeh, Alex C.; Musoke, Rachel N.; Norris, Shane A.; Madise, Nyovani J.; Griffiths, Paula
Abstract Poor breastfeeding practices are widely documented in Kenya, where only a third of children are exclusively breastfed for 6 months and only 2% in urban poor settings. This study aimed to better understand the factors that contribute to poor breastfeeding practices in two urban slums in Nairobi, Kenya. In‐depth interviews (IDIs), focus group discussions (FGDs) and key informant interviews (KIIs) were conducted with women of childbearing age, community health workers, village elders and community leaders and other knowledgeable people in the community. A total of 19 IDIs, 10 FGDs and 11 KIIs were conducted, and were recorded and transcribed verbatim. Data were coded in NVIVO and analysed thematically. We found that there was general awareness regarding optimal breastfeeding practices, but the knowledge was not translated into practice, leading to suboptimal breastfeeding practices. A number of social and structural barriers to optimal breastfeeding were identified: (1) poverty, livelihood and living arrangements; (2) early and single motherhood; (3) poor social and professional support; (4) poor knowledge, myths and misconceptions; (5) HIV; and (6) unintended pregnancies. The most salient of the factors emerged as livelihoods, whereby women have to resume work shortly after delivery and work for long hours, leaving them unable to breastfeed optimally. Women in urban poor settings face an extremely complex situation with regard to breastfeeding due to multiple challenges and risk behaviours often dictated to them by their circumstances. Macro‐level policies and interventions that consider the ecological setting are needed.